Kepatuhan Minum Obat Hipertensi Pada Lansia - Kartini Massa; Leni Arini Manafe (Sam Ratulangi Journal of Public Health, 2021)
Background: Hypertension is a cardiovascular disease that is often found in the elderly, which requires long-term treatment to control, control blood pressure and prevent complications, so medication adherence is required. Elderly compliance in taking antihypertensive drugs is one of the determining factors in controlling blood pressure. The purpose of this study was to determine the description of adherence to taking hypertension medication in the elderly in Wangurer Village. Methode: This is a descriptive study with a cross-sectional design on a population of 32 people, sampling with a total population sampling technique of 32 elderly people with hypertension and taking medication, the research location is in Wangurer Village, North Minahasa Regency in May 2021. Data collection by using a questionnaire, univariate data analysis to see a description of the frequency distribution of adherence to taking hypertension medication in the elderly. Result: This research showed that the characteristics of respondents based on male gender 17 (53.7%) respondents and female sex 15 (46.9%). Age: 60-69 years as many as 22 (68.8%) and age 70-90 years as many as 10 (31.3%). Education: 26 elementary/junior high schools (81.3%), high school 4 (12.5%) and SI 2 (6.3%). Employment, IRT as many as 15 (46.9%), Farmers 14 (43.8%) and retired civil servants as many as 3 (9.3%). Compliance with taking medication for the elderly in Wangurer Village, North Minahasa Regency is in the obedient category as much as 56.3% and in the non-adherent category as much as 43.7%. Conclusion: That can be concluded the most of the elderly in Wangurer Village are obedient to taking hypertension medication.